Study Of Serum Uric Acid Levels In Acute Myocardial Infarction - DR. ABHISHEK DAS,; DR. DHANDAPANI E.,; DR. ARUN SUGUMAR,; DR. ANKIT MANAM, (International Journal of Pharma and Bio Sciences, 2015)
To study the serum uric acid level in patients with acute myocardial infraction.High uric acid level is a negative prognostic factor in patients with myocardial infarction and increases the risk of mortality.We studied patients more than 30 years of age who were diagnosed as ST segment elevation acute myocardial infarction or non-ST segment elevation acute myocardial infarction on the basis of clinical history, examination, ecg changes, biochemical markers, and admitted in sree balaji medical college and hospital.Patients brought to hospital with a history of chest pain and diagnosed as myocardial infraction (both STEMI and NSTEMI) (Diagnosis confirmed by ECG, biochemical markers like Troponin-T, Creatine Kinase (CK-MB). Any patient with a condition known to elevate uric acid level eg. Chronic Kidney Disease, Gout, Haematological malignancy, Hypothyroidism were excluded. Also patients on drugs which increase serum uric acid e.g. Salicylates, Diuretics, Ethambutol . Pyrazinamide and also chronic alcoholics were excluded. Uric Acid levels were high in patients with Acute Myocardial Infarction. Patients who were in higher Killip classification and higher uric acid levels, mortality rate is high in them.